PENGARUH PERAYAAN EKARISTI TERHADAP PEMBENTUKAN SPIRITUALITAS DAN PENDIDIKAN CALON KATEKIS DI STKIP WIDYA YUWANA - Sota, Yulius Sutanggang; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2021)
This study aims to analyze the influence of the Eucharistic celebration on the spirituality and education of prospective catechists at STKIP Widya Yuwana. The methodology used is a literature study with qualitative analysis of various relevant sources regarding the Eucharist and its impact on catechist education. The results of the study indicate that the Eucharistic celebration functions as a source and peak of Christian life, increases spiritual awareness, supports the development of spiritual maturity, and provides motivation in carrying out the calling as a catechist. In addition, the Eucharist plays a role in spiritual healing and strengthening the faith of prospective catechists. In conclusion, the Eucharist has a significant impact on the formation of character and spirituality of prospective catechists.